Numerical and experimental investigation of pulse bubble aeration with high packing density hollow-fibre MBRs. (1st September 2019) - Radaei, Elham; Liu, Xuefei; Tng, Keng Han; Merendino, Giuseppe; Trujillo, Francisco J.; Bérubé, Pierre R.; Leslie, Greg
Abstract: A three-dimensional Computational Fluid Dynamics (CFD) model was developed to study shear stress induced by spherical cap bubbles in hollow fibre (HF) membrane modules configured with a packing density of 38 m 2 /m 3, to predict the shear profile in a commercial hollow fibre membrane module of 265 m 2 /m 3 . The CFD model's computational effort was minimised by simulating the formation of bubble structures and their rising velocities in modules with packing densities of 1.8 and 38 m 2 /m 3 and validated with experimental calibration of shear profiles via electro-diffusion methods (EDM). Pulse bubbles (300 mL) generated from a single sparger at 0.5 Hz produced more satellite bubbles in the wake zone of the leading bubble in high packing density (38 m 2 /m 3 ) than in low packing density modules (1.8 m 2 /m 3 ). The bubble rise velocity was approximately 8% lower in the 38 m 2 /m 3 than in the 1.8 m 2 /m 3 module. Increasing packing density reduced the shear profile from a single sparger and the dispersion of the satellite bubbles in the horizontal plane, especially in the upper part of the membrane module. For systems with multiple spargers, the interaction between pulses generated more shear than the pulses from a single sparger, and produced a more uniform shear profile in the module through asynchronous bubble release from adjacent spargers than synchronous release. A 33% increase in the "Zone of Influence", the flow region where the upward velocity >0.2 m/s, was achieved by moving from a synchronous to an asynchronous form of aeration. Graphical abstract: Image 1 Highlights: CFD model of pulse bubbles in commercial MBRs was developed and validated. Simplification applied and calibrated for high-packed membrane module. Pulse bubbles induced membrane surface shear was investigated. Asynchronous bubble release induced more evenly distributed shear.